First report on natural infection by Dirofilaria repens in a cat in Spain: case report and literature review of feline subcutaneous dirofilariosis in Europe - Sergio Villanueva-Saz; María Victoria Martínez; Sandra Alsina; Antonio Fernández; Álex Gómez; Maite Verde; Héctor Ruiz; Delia Lacasta; Alaa Aldin Alnassan; Michele Trotta; Andrés Yzuel; Diana Marteles (Veterinary Research Communications, 2024)
Dirofilaria repens is an endemic mosquito-borne pathogen widely spread throughout Europe and other non-Europen regions. Infection by D. repens has been reported in dogs, although little is known about the occurrence and epidemiological features of this nematode in cats. During the surgical procedure within the framework of a trap, neuter and release sterilization program, two female filarial nematodes with spontaneous movement were removed from the internal part of the spermatic cord from asymptomatic stray cat in Spain (Grao de Castellón, Castellon de la Plana, province of Spain). Moreover, the presence of microfilariae was detected by using three different methods, including direct blood smear technique, the microhematocrit tube test, and Knott´s modified test. PCR performed from the nematodes extracted from the spermatic cord and from microfilariae in EDTA-blood sample tested both positive for D. repens . To the authors’ knowledge, this is the first report that demonstrates the presence of D. repens in cats in Spain. In this sense, a review of the current scientific status of feline subcutaneous dirofilariosis in Europe was also performed. Future investigations should analyze the epidemiological role of cats in D. repens infection including the prevalence of infection. Veterinarians working in endemic areas should be aware of this infection in cats and their susceptibility.